MENGUNGKAP MUNCULNYA TINDAKAN ACADEMIC DISHONESTY DI KALANGAN MAHASISWA AKUNTANSI - kadek intan mahayuni, Ni; Nyoman Ari Surya Dharmawan; Wiguna, i Gd Nandra Hary (Vokasi : Jurnal Riset Akuntansi, 2025)
Academic dishonesty among students has become a major concern in Indonesian higher education, as academic fraud serves as a predictor of corruption levels in a country. This study aimed to explore and analyze the reasons behind academic dishonesty practices among students using the Theory of Reasoned Action and Fraud Diamond as theoretical frameworks. A qualitative method with a case study approach was employed, where data were collected through observation, interviews with accounting students and lecturers at the Faculty of Economics, Undiksha, and documentation. The findings reveal that technological developments, particularly AI (ChatGPT), significantly impact learning methods. Students utilize AI to complete assignments quickly and efficiently, yet this usage potentially creates long-term dependency and academic fraud such as plagiarism and ghostwriting services. Academic pressure from accumulated tasks and tight deadlines becomes the primary trigger for students seeking instant solutions. The monotonous learning system lacking practical application drives students to suggest improvements in time flexibility, active lecturer involvement, and theory-practice balance to prevent academic dishonesty.